Validity and reliability of the Fear COVID-19 Scale (FCV-19S) instrument in mexican nurses - Cárdenas-Rodríguez, Maritza Lizeth (2022)
Objective: To determine the validity and reliability of the FCV-19S in Mexican nurses. Method: Quantitative study was carried out in a population of nurses working in public hospitals in Mexico, the final sample of 129 participants residing in different states of the country. The validated instrument was the COVID-19 Fear Scale. A confirmatory factor analysis was performed to determine validity, and the internal consistency reliability was subsequently determined by Cronbach's α. Main results: From the factor analysis the instrument shows that all items saturate the same factor and are related to each other. The sample adequacy measure confirms the correlations between variables and the mediation of the same factor (KMO= .846). The reliability of the scale is satisfactory (α= 0.845). Overall conclusion: The FCV-19S shows validity and reliability to assess fear of COVID-19 in the Mexican nursing population.